Immunostimulation by Lactobacillus kefiri S-layer proteins with distinct glycosylation patterns requires different lectin partners - Malamud, Mariano (2020)
S-layer (glyco)-proteins (SLPs) form a nanostructured envelope that covers the surface of different prokaryotes and show immunomodulatory activity. Previously, we have demonstrated that the S-layer glycoprotein from probiotic Lactobacillus kefiri CIDCA 8348 (SLP-8348) is recognized by Mincle (macrophage inducible C-type lectin receptor) and its adjuvanticity depends on the integrity of its glycans. However, the glycan´s structure has not been described so far. Herein, we analyze the glycosylation pattern of three SLPs, SLP-8348, SLP-8321, and SLP-5818, and explore how these patterns impacts their recognition by Ctype lectin receptors (CLRs) and the immunomodulatory effect of the L. kefiri SLPs on antigen-presenting cells. HPAEC-PAD performed after β-elimination showed glucose as the major component in the O-glycans of the three SLPs, however, some differences in the length of hexose chains were observed. No N-glycosylation signals were detected in SLP-8348 and SLP-8321, but SLP5818 was observed to have two sites carrying complex N-glycans based on a site-specific analysis and a glycomic workflow of the permethylated glycans. SLP-8348 was previously shown to enhance LPS-induced activation on both RAW264.7 macrophages and murine BMDCs; we now show SLP-8321 and SLP-5818 have a similar effect regardless of the differences in their glycosylation patterns. Studies performed with BMDCs from CLR-deficient mice revealed that the immunostimulatory activity of SLP-8321 depends on its recognition by Mincle, whereas SLP-5818’s effects are dependent on SignR3 (murine ortholog of human DC-SIGN). These findings encourage further investigation of both the potential application of these SLPs as new adjuvants and the protein glycosylation mechanisms in these bacteria.